2011
DOI: 10.1177/0969733011398099
|View full text |Cite
|
Sign up to set email alerts
|

Rationing home-based nursing care: professional ethical implications

Abstract: The purpose of this study was to investigate nurses' decisions about priorities in home-based nursing care. Qualitative research interviews were conducted with 17 nurses in home-based care. The interviews were analyzed and interpreted according to a hermeneutic methodology. Nurses describe clinical priorities in home-based care as rationing care to mind the gap between an extensive workload and staff shortages. By organizing home-based care according to tight time schedules, the nurses' are able to provide car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(112 citation statements)
references
References 23 publications
2
100
0
10
Order By: Relevance
“…This philosophy could be influenced by a range of factors such as education and training, working environment and the profession as a whole. Several qualitative studies offered a different explanation of nurses' choices when they have access to limited resources in health care (Halvorsen et al ., ; Nortvedt et al ., ; Tonnessen et al ., ). The results of these studies support that nurses may feel that humanistic and holistic care is not realistic within such context and may subsequently develop their own personal standards of care, which are heavily influenced by a biomedical ethos to cope with such limitations.…”
Section: Discussionmentioning
confidence: 97%
“…This philosophy could be influenced by a range of factors such as education and training, working environment and the profession as a whole. Several qualitative studies offered a different explanation of nurses' choices when they have access to limited resources in health care (Halvorsen et al ., ; Nortvedt et al ., ; Tonnessen et al ., ). The results of these studies support that nurses may feel that humanistic and holistic care is not realistic within such context and may subsequently develop their own personal standards of care, which are heavily influenced by a biomedical ethos to cope with such limitations.…”
Section: Discussionmentioning
confidence: 97%
“…Tønnessen et al. () found that some nurses perceive their only responsibility is to provide services described in the decisions. Nurses in this study safeguarded needs beyond patients’ predefined decisions, expressing that they felt responsible for the patients’ overall well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other professional health care organizations (Shortell & Kaluzny, 2006), over the past few decades many Dutch agencies have merged in an attempt to counter the effect of budget cuts (Postma, Oldenhof, & Putters, 2015 process has resulted in large, hierarchically managed agencies. As agencies have increased in size, so has the tendency to introduce "Tayloristic notions" in care (Da Roit, 2013;Nies et al, 2013;Postma et al, 2015): caregiving is characterized by a focus on efficiency and productivity, standardization of work processes and differentiation of tasks (Mintzberg, 1979;Tønnessen, Nortvedt, & Førde, 2011;Van der Boom, 2008), with tasks being assigned to "different care workers, depending on required professional capabilities" (Postma et al, 2015, p. 67). …”
Section: Home Care Agencies In the Netherlandsmentioning
confidence: 98%